Challenges and issues of the right to vote of the Haitian diaspora - (:unkn) unknown (My University, 2025)
The recurrent crisis that Haiti has gone through throughout its history have led to migratory movements of Haitians to other territories. At first, Haitian migration was concentrated in the Caribbean countries, especially Cuba and the Dominican Republic, then it spread to other countries over the years. Under the dictatorship of Francois Duvalier and his son Jean-Claude successively, many intellectuals fled the country due to political persecution and the brutality of the regime. These Haitians have settled in Canada, especially in the francophone part; in the United States particularly in New York and Boston; in France, Paris and African countries. During the 1980s, more and more Haitians fled the country, not only because of the dictatorship, but also because of poverty, unemployment, and deteriorating living conditions in the country. A dynamic diaspora of Haitians from abroad is currently contributing to the development of the country through remittances. Being in considerable numbers and interested in the governance of the country, the Haitian diaspora aspires to play a decisive role in the future of Haiti. Participating in the decision-making process requires legal recognition of their full citizenship status, which provides all the benefits that come with it, including the right to vote. This study aims to examine the challenges and issues related to the right to vote of the Haitian diaspora. It also intends to analyze the practical aspects of the issue in order to make useful recommendations to the relevant institutions.
Keywords: African Research